ChemInform Abstract: Effects of Ultrasound and Microwaves on Selective Reduction: Catalyst Preparation and Reactions. Issue 1 (January 2015) - Wu, Zhilin; Borretto, Emily; Medlock, Jonathan; Bonrath, Werner; Cravotto, Giancarlo
Abstract Review: 145 refs.